A Workshop on Writing a Systematic Literature Review Using Artificial Intelligence (AI)-Based Tools - Emilius German; Rijal Hakiki; Ani Pujiastuti; Disa Evawani Lestari; Risa Fitria (ACADEMICS IN ACTION Journal of Community Empowerment, 2024)
To generate meaningful research, lecturers and investigators have to identify strong, innovative research ideas. However, they often have difficulty with digesting a large number of relevant studies when conducting literature review. The workshop on "Writing a Systematic Literature Review Using New Tools" was intended to provide academics and professors with cutting edge techniques and resources to improve the efficiency and quality of their literature reviews. Participants were provided with tools including Publish or Perish, Mendeley, and Rayyan to help with systematic review processes, reference management, and collecting bibliographic data. The workshop offered information and practical exercises so that attendees could use these tools directly. Participants' comments indicated notable progress in their capacity to organize data, carry out systematic evaluations, and efficiently pinpoint research gaps. Most attendees gave the course high marks for efficacy; most of them scored between 4 and 5. This favorable response highlights how well the workshop improved the participants' research abilities and tool competency, which raised the standard for academic research and publishing.